Managemen Pengelolaan Kelas di TK Kartika II-26 Bandar Lampung (PIAUD IAIN Kudus, 2019)
This study aims to describe the application of classroom management in TK Kartika II-26 Bandar Lampung. This research is a descriptive study with a qualitative approach. Data collection methods used are the method of observation, interviews, and documentation. The results showed that the management of classroom management used by educators in TK Kartika II-26 Bandar Lampung was (1) arrangement of room facilities and infrastructure tailored to the activities to be carried out (2) grouping of tables and chairs according to children's needs so that they had space more flexible motion (3) The arrangement of table chairs can change, when participating in activities, children do not always sit in a chair, but can also sit on the floor / carpet, (4) Walls can be used to attach facilities used as learning resources and results children's activities but not too much so as not to disturb the child's attention, (5) Laying and storing playground equipment is arranged in such a way that it can train children to get used to habituation such as independence, responsibility, making decisions, customizing equipment and so on, play tools for safety activities are arranged in ruanga n, so that it can function if needed by students, (6) Classes for kindergarten children need to be designed fun. Bright and cheerful colors are loved by children. However, do not overcrowd the color because it can distract the child and (7) the sun's light can try to enter properly so the class is not dark.